Overview of Granular Cell Tumor General Hospitals in Iraq over 11-years - AL-Kafaji, Raid Razak Ali; Ali, Thaer Kassim (Technium BioChemMed, 2024)
Granular cell tumor is rare tumors from Schwann cells with clinicopathological feature results, which may be showed in both benign and malignant tumor. Several tumors commonly appear in the oral cavity, gastrointestinal tract and skin. This must be appropriately treated to avoid repetition or metastatic cancer lesions. The aim study is to search clinicopathological aspects of granular cell tumor diagnosed at different general hospitals in Iraq and to compare these findings with epidemiological findings from different governorates positions. The data was collected from different Iraq governorates in mouth and tongue area from 2010 to 2020 years. Different parameters were displayed like age group, gender, topography, morphology and distribution of annual patients of the tumor. According to the available of the all information about these characteristics was revealed the inclusion criteria. The factors frequencies were calculated from descriptive analysis of the data. The total (101) cases of granular cell tumor in mouth and tongue location were found. (17) cases was the maximum value in 2015 year and it followed by (15) cases in 2019 year as compared to other years. Baghdad governorate (95) cases has a greatly patients than other governorates. (59) Cases with (58.40 %) of female gender and (42) cases with (41.60) of male and the female to male ratio was (1.38:1).